Morphological and physiological responses of rice (Oryza sativa) to limited phosphorus supply in aerated and stagnant solution culture - N. Insalud (2018)
Background and Aims: Rain-fed lowland rice commonly encounters stresses from fluctuating water regimes and nutrient deficiency. Roots have to acquire both oxygen and nutrients under adverse conditions while also acclimating to changes in soil-water regime. This study assessed responses of rice roots to low phosphorus supply in aerated and stagnant nutrient solution. Methods: Rice (Oryza sativa 'Amaroo') was grown in aerated solution with high P (200 μm) for 14 d, then transferred to high or low (1·6 μm) P supply in aerated or stagnant solution for up to 8 d. Key Results: After only 1 d in stagnant conditions, root radial oxygen loss (ROL) had decreased by 90 % in subapical zones, whereas near the tip ROL was maintained. After 4 d in stagnant conditions, maximum root length was 11 % less, and after 8 d, shoot growth was 25 % less, compared with plants in aerated solution. The plants in stagnant solution had up to 19 % more adventitious roots, 24 % greater root porosity and 26 % higher root/shoot ratio. Rice in low P supply had fewer tillers in both stagnant and aerated conditions. After 1-2 d in stagnant solution, relative P uptake declined, especially at low P supply. Aerated roots at low P supply maintained relative P uptake for 4 d, after which uptake decreased to the same levels as in stagnant solution. Conclusions: Roots responded rapidly to oxygen deficiency with decreased ROL in subapical zones within 1-2 d, indicating induction of a barrier to ROL, and these changes in ROL occurred at least 2 d before any changes in root morphology, porosity or anatomy were evident. Relative P uptake also decreased under oxygen deficiency, showing that a sudden decline in root-zone oxygen adversely affects P nutrition of rice. © The Author 2006. Published by Oxford University Press on behalf of the Annals of Botany Company. All rights reserved.